Duplication unilateral femoral vein - Ferreira Arquez, Humberto (Bangladesh Journal of Medical Science, 2015)
Background: The purpose of this paper is to describe a case of duplication of unilateral femoral vein, with a complete extension of duplicated veins with similar diameters which is an uncommon condition, noticed in fewer than 10% of lower limb. The venous anatomy is highly variable, only 1/6 patients are exempt of these anomalies. One is the duplicity of the femoral vein. The classic anatomic venous in the lower limb is found in only 16% of subject. Methods: Anatomical variation in the lower limb was found during routine dissection in a 75-year-old male cadaver in the Morphology Laboratory at the University of Pamplona. Result: In the adductor canal femoral vein was divided into two veins: one medial and other lateral, which ascended in parallel until the femoral triangle, at this level 6.5 cms below the inguinal ligament the femoral vein- lateral ramus received to the lateral circumflex femoral vein, and received to the medial circumflex femoral vein, followed the femoral veins lateral ramus binds to the femoral veins medial ramus forming common femoral vein. Both Femoral Veins extend from the adductor canal to the femoral triangle had a length of 18 cms. The caliber of the femoral vein and the caliber of common femoral vein was 30 mm. The caliber of the femoral artery at the femoral triangle was 24 mm. The caliber of the femoral medial and lateral venous component was 20 mm. The common femoral vein received posterolateral to the deep femoral vein; The common femoral vein received anteromedial at the great saphenous. Conclusion: Knowledge of the truncular venous variations is important for the investigation of the venous network. It is also important to recognize and avoid potential errors in diagnosis of deep venous thrombosis of the femoral vein, in the case of an occluded duplicated trunk. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.292-296